1984
DOI: 10.1530/jrf.0.0710107
|View full text |Cite
|
Sign up to set email alerts
|

Role of LH pulse amplitude in controlling rat ovarian oestradiol-17  secretion in vitro

Abstract: Ovaries from di-oestrous rats were removed and placed in perifusion culture: 4-6 ovaries were cultured for 3 h with (1) no gonadotrophin; (2) tonic FSH (200 ng/ml); (3) tonic LH (30 ng/ml); (4) tonic FSH and tonic LH; (5) tonic FSH and hourly pulses of 40 ng LH/ml; or (6) tonic FSH and hourly pulses of 50 ng LH/ml. The total amount of LH administered was 3060 ng LH, regardless of mode of delivery. Perifusate was collected every 10 min and assayed for oestradiol-17 beta by RIA. The total amount of oestradiol-17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Less frequent pulsatile administration of FSH at either concentration did not enhance SCC mRNA accumulation above basal. Our inferences regarding this molecular endpoint of FSH action are in agreement with previous functional studies that demonstrated that pulses of gonadotropins are more efficacious than continuous hormone exposure in increasing ovarian steroid production, follicular development, and luteinization [26][27][28][29][30]35]. The fractional increases in SCC mRNA accumulation observed here under perifusion conditions are consistent with the magnitude of the increases reported during static culture of porcine granulosa cells [36].…”
Section: Cyclic Amp Responsessupporting
confidence: 91%
See 1 more Smart Citation
“…Less frequent pulsatile administration of FSH at either concentration did not enhance SCC mRNA accumulation above basal. Our inferences regarding this molecular endpoint of FSH action are in agreement with previous functional studies that demonstrated that pulses of gonadotropins are more efficacious than continuous hormone exposure in increasing ovarian steroid production, follicular development, and luteinization [26][27][28][29][30]35]. The fractional increases in SCC mRNA accumulation observed here under perifusion conditions are consistent with the magnitude of the increases reported during static culture of porcine granulosa cells [36].…”
Section: Cyclic Amp Responsessupporting
confidence: 91%
“…More direct assessments of the role of pulsatile gonadotropin secretion on ovarian function have utilized perifusion systems. Peluso et al [26,27] observed that whole rat follicles secreted increased amounts of estradiol and had an increased proportion of mid-sized growing follicles when exposed to pulsatile versus tonic FSH stimuli. Furthermore, Peluso and Steger suggested that the effect of LH pulses given in the presence of a constant infusion of FSH depended on a threshold concentration of LH, as well as the rate of increase in LH concentrations [28].…”
Section: Introductionmentioning
confidence: 99%
“…LH is released in a pulsatile manner, and the frequency and amplitude of these pulses vary across the reproductive cycle in response to ovarian steroidogenic feedback. The pulse frequency of LH dictates the amounts of steroid hormones produced, where each pulse of LH is followed by an increase in androstenedione and estradiol secreted from the ovary in many species (Baird et al 1976, 1981, Peluso et al 1984. When theca cells were cultured in vitro, low levels of LH also stimulated androgen production (Campbell et al 1998, Ryan et al 2008, whereas, at high doses, LH inhibited androstenedione production and stimulated progesterone secretion as well as changing cell morphology indicating that the high LH levels induced luteinization in these cells (Campbell et al 1998).…”
Section: Steroidogenesismentioning
confidence: 99%
“…Much of the current research suggests an indirect effect of glucose on ovarian function via nutritionally induced metabolic hormones such as insulin, insulin-like growth factor 1 (IGF1) and leptin (Peluso et al 1984, Davis et al 1990, Munoz-Gutierrez et al 2002. Conversely, glucose may also act directly on the ovary.…”
Section: Introductionmentioning
confidence: 99%